A regularization approach to blind deblurring and denoising of QR barcodes - van Gennip, Yves; Athavale, Prashant; Gilles, Jérôme; Choksi, Rustum (Institute of Electrical and Electronics Engineers, 2015)
QR bar codes are prototypical images for which part of the image is a priori known (required patterns). Open source bar code readers, such as ZBar, are readily available. We exploit both these facts to provide and assess purely regularization-based methods for blind deblurring of QR bar codes in the presence of noise.